2012
DOI: 10.1007/s00262-012-1324-3
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone and Gemcitabine in combination reduces immune suppression and modulates T cell populations in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDA) is a leading cause of cancer mortality with a dismal 2–5% 5-year survival rate. Monotherapy with Gemcitabine has limited success, highlighting the need for additional therapies that enhance the efficacy of current treatments. We evaluated the combination of Gemcitabine and Rosiglitazone, an FDA-approved drug for the treatment of type II diabetes, in an immunocompetent transplantable mouse model of pancreatic cancer. Tumor progression, survival and metastases were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…These data are in accordance with earlier works performed in the subcutaneous model of PDAC. 25,26 Interestingly, we found for the first time that tumor progression was accompanied by an enrichment of granulocytic MDSC but simultaneously by a decrease in the frequency of monocytic MDSC. In different tumor models, the proportion of granulocytic and monocytic MDSC subsets is highly variable and depends on factors that have not yet been well investigated.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…These data are in accordance with earlier works performed in the subcutaneous model of PDAC. 25,26 Interestingly, we found for the first time that tumor progression was accompanied by an enrichment of granulocytic MDSC but simultaneously by a decrease in the frequency of monocytic MDSC. In different tumor models, the proportion of granulocytic and monocytic MDSC subsets is highly variable and depends on factors that have not yet been well investigated.…”
Section: Discussionmentioning
confidence: 77%
“…13,25,26 Using an orthotopic Panc02 model of murine PDAC, we revealed a strong accumulation of both immunosuppressive monocytic and granulocytic subpopulations of MDSC in the tumor microenvironment and lymphatic organs. These data are in accordance with earlier works performed in the subcutaneous model of PDAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic cancer is one of the most deadly malignancies among all types of cancers with a five-year survival rate of less than 6% in the United States [2,3]. Successful translation of potential cancer therapies into clinics will mainly depend on targeted drug delivery approaches with high safety margin.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that patients treated with gemcitabine had significantly lower levels of the immunosuppressive molecule TGFb, Tregs, and MDSCs but an increased number of DCs, monocytes, and activated T-cells. 46,47 CLL is commonly treated with fludarabine, bendamustine, and lenalidomide. 48 While both fludarabine and bendamustine are immunosuppressive per se, lenalidomide enhances the degradation of Ikaros 1 and 3.…”
Section: Conditioning Of Patients Receiving Car T-cell Therapymentioning
confidence: 99%